Cholesterol-Lowering Efficacy of Plant Sterols/Stanols Provided in Capsule and Tablet Formats: Results of a Systematic Review and Meta-Analysis - Amir Shaghaghi, Mandana; Abumweis, Suhad S.; Jones, Peter J.H. (Journal of the Academy of Nutrition and Dietetics, 2013)
Plant sterols/stanols-enriched foods possess well-documented low-density lipoprotein (LDL)-cholesterol−lowering effect. However, the relative efficacy of plant sterols/stanols as supplements (tablets/capsules) compared with other dietary forms still needs to be determined. Our aim was to precisely identify and quantify the LDL-cholesterol−lowering effect of plant sterols/stanols as supplements in contrast to food-based approaches. Eight eligible clinical trials published from January 1992 to April 2013 were identified from five databases. A random effect model was used to calculate weighted mean effect sizes for net differences in LDL-cholesterol concentrations. Among the included trials with the duration between 4 and 6 weeks, plant sterol/stanol dose ranged from 1.0 to 3.0 g/day administrated mainly with the main meals (2 or 3 times/day). Intake of plant sterol/stanol supplements decreased LDL-cholesterol concentrations by 12 mg/dL (0.31 mmol/L) (95% CI −0.39 to −0.23; P<0.000) compared with placebo. The test of heterogeneity was not significant (χ2 , P=0.50, I2=0%). Further analysis showed no significant difference between the LDL-cholesterol−lowering action of plant sterols/stanols supplements (−12 mg/dL [−0.31 mmol/L]; 95% CI −0.39 to −0.24; P<0.0001) vs foods enriched with plant sterols/stanols (−12 mg/dL [−0.31 mmol/L]; 95% CI −0.35 to −0.27; P<0.0001). Plant sterol/stanol supplements as part of a healthy diet represent an effective means of delivering LDL-cholesterol−lowering similar to plant sterols/stanols delivered in various food formats.